The Phonomotor Approach to Treating Phonological-Based Language Deficits in People With Aphasia. - Kendall, Diane L.; Nadeau, Stephen E. (Topics in Language Disorders)
The phonomotor treatment program for treating word-retrieval deficits among people with aphasia is inspired by a parallel distributed processing model of lexical processing and is focused at the level of individual phonemes and phoneme sequences. Because verbal production of words involves the translation of a lexical-semantic representation into phonological representations, training the repertoire of phonological sequences should enable individuals with anomia to regain the ability to learn words and sequences, generalize to linguistic items not trained, and continue growth following treatment termination. The development and refinement of the phonomotor treatment program, which began in 2000, have followed the 5-phase model for communication disorders and sciences framework outlined by R. Robey (2004). To date, there have been 8 published articles on the phonomotor treatment program. A large-scale randomized trial comparing phonomotor with standard of care for word-retrieval deficits is underway. The goal of this article is to review the theoretical framework, treatment procedures, current evidence, and future directions of the phonomotor protocol.